Slowly resolving global myocardial inflammation/oedema in Tako-Tsubo cardiomyopathy: evidence from T2-weighted cardiac MRI. Issue 17 (11th July 2012) - Neil, Christopher; Nguyen, Thanh Ha; Kucia, Angela; Crouch, Benjamin; Sverdlov, Aaron; Chirkov, Yuliy; Mahadavan, Gnanadevan; Selvanayagam, Joseph; Dawson, Dana; Beltrame, John; Zeitz, Christopher; Unger, Steven; et al.
Abstract : Objective: Tako-Tsubo cardiomyopathy (TTC) is associated with regional left ventricular dysfunction, independent of the presence of fixed coronary artery disease. Previous studies have used T2-weighted cardiac MRI to demonstrate the presence of periapical oedema. The authors sought to determine the distribution, resolution and correlates of oedema in TTC. Patients: 32 patients with TTC were evaluated at a median of 2 days after presentation, along with 10 age-matched female controls. Extent of oedema was quantified both regionally and globally; scanning was repeated in patients with TTC after 3 months. Correlations were sought between oedema and the extent of hypokinesis, catecholamine release, release of N-terminal prohormone of B-type natriuretic peptide (NT-proBNP), and markers of systemic inflammatory activation (high-sensitivity C-reactive protein and platelet response to nitric oxide). Results: In the acute phase of TTC, T2-weighted signal intensity was greater at the apex than at the base (p<0.0001) but was nevertheless significantly elevated at the base (p<0.0001), relative to control values. Over 3 months, T2-weighted signal decreased substantially, but remained abnormally elevated (p<0.02). The regional extent of oedema correlated inversely with radial myocardial strain (except at the apex). There were also direct correlations between global T2-weighted signal and (1) plasma normetanephrine (r=0.39, p=0.04) and (2) peak NT-proBNP (r=0.39, p=0.03), but not with systemic inflammatory markers. Conclusions: TTC is associated with slowly resolving global myocardial oedema, the acute extent of which correlates with regional contractile disturbance and acute release of both catecholamines and NT-proBNP.